Identification and expression analysis of Th2 immune-related gene IL4/13A in turbot (Scophthalmus maximus) - Huo, Huanhuan; Liu, Baoliang; Wang, Zirui; Zhou, Qiubai (Frontiers in Immunology, 2024)
Th2 immunity is a primary host defense against extracellular pathogens, and different IL4/13 paralogues are involved in this immune response in fish. Here, we identified IL4/13A for further Th2 immune response providing information in turbot. The results showed that the full length of the IL4/13A gene is 1,333 bp, containing a 432-bp open reading frame (ORF) that encoded 144 amino acids. Phylogenetic analysis recently showed that turbot IL4/13A has a relationship with Dicentrarchus labrax. Moreover, syntenic analysis revealed similar neighboring genes associated with turbot IL4/13A, compared with other teleosts and mammals. In addition, IL4/13A was widely expressed in all examined tissues with the highest expression level in skin, followed by liver and gill. Finally, IL4/13A showed a general trend of upregulation in immune tissues following bacterial challenge. The significant quick induction of IL4/13A indicated its key roles to prevent pathogens. Characterizations of IL4/13A will probably contribute to understanding of Th2 immunity in fish.